Silica fume mixed concrete in acidic environment. (2020) - Tripathi, Deep; Kumar, Rakesh; Mehta, P.K.; Singh, Amrendra
Abstract: When concrete is exposed to aggressive environment, its durability may get affected. Earlier, people were more concerned about the strength of concrete without thinking about its durability. But at present the durability of concrete and concrete structures has become a major concern. In this experimental study, the effect of Nitric Acid on concrete made using Silica Fume (SF) was investigated. The optimum replacement level of Ordinary Portland Cement (OPC) with Silica Fume in respect of compressive strength was found i.e. 20%. After obtaining the optimum replacement level, cubes of size 100 mm were cast for both the Normal Concrete (NC) and Silica Fume Mixed Concrete (SFMC) for further studies. All the concrete samples were tested for the strength and durability under acidic environment (8% Nitric acid exposure for a maximum of 90 days). It was found that the compressive strength of all the concrete mixtures decreases in acidic environment for all the exposure periods. The weight loss in both the specimen (NC and SFMC) is more in Nitric acid and it increases with exposure period. It was concluded that Silica Fume Mixed Concrete was more durable than Normal Concrete in acidic environment.